2019
DOI: 10.1016/j.ins.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Reliable location allocation for hazardous materials

Abstract: Highlights• A reliable location allocation model for hazardous materials is formulated.• Scenario of depot disruption is considered.• Numerical examples show that the proposed model leads to 8.33Abstract Decision-making on location allocation has gained considerable attention since it involves strategic and operational policies with mid-term and long-term effects. In this paper, a reliable location allocation mechanism in the context of hazardous materials is proposed, considering that the depots are subject t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Prior studies on hazardous material logistics management have primarily focused on problems concerning: risk assessment (Erkut and Ingolfsson 2000;Hu et al 2020a), vehicle routing Du, Yu, and Li 2016), location allocation (Fan et al 2019), inventory routing (Hu, Li, and Li 2018;Hu et al 2020b), and supply chain network design (Ma and Li 2018). Different from MDVRPs devised to transporting ordinary goods, hazmat MDVRPs usually consider risk as the main optimisation objective, which directly affects decisions for route selection and retailer assignment.…”
Section: Hazmat Mdvrps With Risk Minimisationmentioning
confidence: 99%
“…Prior studies on hazardous material logistics management have primarily focused on problems concerning: risk assessment (Erkut and Ingolfsson 2000;Hu et al 2020a), vehicle routing Du, Yu, and Li 2016), location allocation (Fan et al 2019), inventory routing (Hu, Li, and Li 2018;Hu et al 2020b), and supply chain network design (Ma and Li 2018). Different from MDVRPs devised to transporting ordinary goods, hazmat MDVRPs usually consider risk as the main optimisation objective, which directly affects decisions for route selection and retailer assignment.…”
Section: Hazmat Mdvrps With Risk Minimisationmentioning
confidence: 99%
“…Ma et al [37][38][39] developed the multi-objective robust optimization model with maximum local risk constraint for hazmat transportation. Other studies on hazmat transportation risk may be found in literature [40][41][42][43].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They proposed a chance-constrained programming model that produced an optimized balance between transportation risk and cost. Fan et al (68) developed an integer linear programming model for the reliable location-routing of hazmat, in which they considered the depot disruption when deciding on depot location. Hu et al (69) introduced a multi-objective optimization method for finding the hazmat warehouse locations and the routes under the constraint of traffic restrictions in inter-city roads.…”
Section: Facility Locationmentioning
confidence: 99%